Konsep Kafa’ah Dalam Pernikahan Menurut Hukum Islam - Nursaniah Harahap; Faisar Ananda Arfa (Jurnal Ilmiah Wahana Pendidikan, 2023)
Marriage will achieve peace, tranquility, happiness and serenity both physically and mentally, known as sakinah, mawaddah warohmah, it needs to be well planned and mature. The thing that must be planned is someone who is chosen to be used as a life partner, that person must meet the criteria set both in Islam and other rules. The purpose of this study is to reveal the concept of sekufu in determining companions according to Islamic teachings. This type of research is library research, namely research that focuses on literature by analyzing the content of some related literature. Results of the discussion Choosing a mate is part of the sunnah recommended by the Prophet Muhammad, he said "Women are married in general on the basis of four factors: wealth, social status (rank), beauty, and strength of religion; choose a woman who is strong in her religion, you must be lucky.” Of the 4 recommendations of the Prophet SAW above, in fact it is part of a person in choosing a mate that must be equal or sekufu'. In choosing a mate, the Prophet Muhammad emphasized to find someone who has good religious practices. Islam emphasizes that in marriage not only see worldly elements, pleasure alone, but there is a way to foster a life that is prosperous, eternal and of course morals to teach offspring to become successors of Islamic teachings.